Halal Cosmetic Products and Implications for the validity of Prayers within the framework of MUI Fatwa No. 26 of 2013 - Pramita, Adinda Dian; Sasono, Muhammad Farras Shafwan (ASEAN Journal of Halal Study, 2024)
This research uses a qualitative method with a descriptive narrative approach to understand the existing situation through an inductive thinking process. The focus of this research is to integrate Islamic principles into halal cosmetic product innovation, specifically on Wardah Foundation Colorfit Matte Foundation variant. The research method involves an in-depth literature review, including analysis of Qur'anic verses, hadith, 4Mazhab as well as MUI Fatwa No. 26 of 2013. The research process includes issue identification, subject determination, and reflection on the research results. The results show that Wardah Foundation has met the halal standards in accordance with Islamic law, but it is important to consider the use of this product in the context of ablution and prayer. This product has a waterproof composition that can prevent water from reaching the skin, thus potentially affecting the validity of wudhu and prayer according to the views of certain madhhabs. This study emphasizes that manufacturers of halal cosmetics need to pay attention not only to the halalness of the ingredients but also the impact of their use in worship.